Modern approaches to the correction of dysbiotic intestinal disorders in children with chronic pyelonephritis - T.O. Kryuchko; V.P. Harshman; I.M. Nesina; N.V. Kuzmenko (Zaslavsky O.Yu., 2017)
Background. It is known that more than 80 % of children with chronic pyelonephritis (СP) have abnormal intestinal disorders, which requires correction and recovery of microflora by inclusion of probiotics into therapeutic and prophylactic regimens. The purpose of the study was to study the effectiveness of probiotic Subalin in the comprehensive treatment of СP in preschool children. Materials and methods. We examined 40 children aged 0 to 6 years with a primary СP and preserved kidney function. Group I of patients received standard therapy according to the protocol. Bifido- or lactobacilli were used to correct the dysbiosis in children of this group. Patients of group II received basic therapy in combination with probiotic Subalin according to the scheme suggested by us. The rate of elimination of intoxication and dyspeptic syndromes, duration of clinical and laboratory remission of the underlying disease were assessed. Results. Evaluation of clinical effectiveness of Subalin in children for 1 month showed its more significant effectiveness in eliminating the main manifestations of dysbiosis. A significantly more pronounced frequency of normalization of feces was revealed on the background and after treatment with Subalin, in contrast to the comparison group. There was a tendency to decrease in duration (p ≤ 0.1) and a significant (p < 0.05) decrease in manifestations of intoxication syndrome in children of group II. During the 6 months of follow-up, 94.7 % of the children in group II had a significantly higher antiretroviral effectiveness of the therapy, and the duration of complete clinical and laboratory remission was 5.9 ± 0.4 months, compared with the identical indices in group I (66.7 % and 3.1 ± 0.1 months, respectively). Conclusions. The obtained results confirmed the expediency of using Subalin in the comprehensive treatment of CP in children of preschool age.